Immunocytochemistry and DNA-Image Cytometry in Diagnostic Effusion Cytology I. Prevalence of Markers in Tumour Cell Positive and Negative Smears - Helma Motherby; Mary Kube; Nikolaus Friedrichs; Bahram Nadjari; Kristiane Knops; Andreas Donner; Betty Baschiera; Peter Dalquen; Alfred Böcking (Analytical Cellular Pathology)
To determine the prevalence of immunocytochemical positivities for a panel of antibodies in benign and malignant cells in effusions with known follow‐up in order to use these as diagnostic markers. Besides their ability to identify malignant epithelial cells their contribution to the differential diagnosis between carcinomatoses and mesotheliomas was investigated. 101 tumour cell positive and 53 negative effusions were stained with 12 different antibodies. Results were scored semiquantitatively per cell type. Furthermore, DNA‐image cytometry was performed. While prevalence of Ber‐EP4 positivity was 95.4% in metastatic carcinoma cells, it was 0% in those from mesotheliomas. No cell type reacted with this marker in benign effusions (0%). Ber‐EP4 correctly differentiated between metastatic carcinoma and mesothelioma in 98.0%. Prevalence of DNA‐aneuploidy was 95.4% in metastatic carcinomas, 57.1% in mesotheliomas and 0% in reactive effusions. Combining immunocytochemistry (Ber‐EP4 positivity) and DNA‐image cytometry (aneuploidy) results in a 100% detection of metastatic carcinomatoses and 57.1% of mesotheliomas. Both markers furthermore allowed a correct differentiation of these entities in 98%.